Enabling the Triple Helix Model Through the Implementation of Smart Specialization: the Case of Ukraine - YEGOROV, I.; GRYGA, V.; RYZHKOVA, Yu. (Science and Innovation, 2022)
Introduction. Euro-integration determines the need to harmonize the innovation policy of Ukraine in line with smart specialization (SS). SS is a quite new tool to facilitate knowledge-based growth in regions. Problem Statement. SS aims at stimulating new economic activities that emerge at the intersection of interests of many different stakeholders. The SS implementation in Ukraine started from pilot activities in 3 regions, in 2017. Their results were not considered properly while incorporating SS into regional development strategies. Despite technical support from the European Commission, many regions were not able to change the policy making process and to ensure proper triple helix (TH) interactions. The under-involvement of the state in the process is among the reasons thereof, so the role of the state in SS has been explained in the paper too. Purpose. The purpose of this research is to assess the SS implementation in Ukraine in the context of TH interaction between innovation stakeholders. Materials and Methods. The study is based on the data obtained by the authors during the elaboration of smart specialization for Kyiv city and Kyiv Oblast, the analysis of the regulatory framework, as well as other analytical materials and research papers. The expert opinion generalization, content and statistical analysis methods have been used. Results. The first steps in the implementation of the SS concept in the strategies of regional development have been assessed, the problems and ways to address them have been identified in order to facilitate the SS and to strengthen TH cooperation in Ukraine. The current situation with the implementation of SS has been analyzed. The analysis has shown paths for assessing the Ukrainian innovation capacity, international developments, and the development of the existing essential tools to control the progress in the promotion of smart specialization in the country. The report on the development of SS in Kyiv and Kyiv Oblast with an emphasis on the problems related to the involvement of stakeholders has been prepared. Conclusions. The key barriers for the SS implementation, namely, inconsistency of the legislation, underdeveloped innovation and industrial policies have been identified and the ways for overcoming these barriers have been proposed.